Surgery for advanced oropharyngeal cancer - A. V. Karpenko; R. R. Sibgatullin; A. A. Boyko; N. S. Chumanikhina; E. Yu. Lomteva; M. V. Lavrova; M. G. Kostova; O. M. Nikolayeva (Опухоли головы и шеи, 2018)
The study objective is to assess the results of this approach and identifications of factors that may influence the effectiveness of such an approach.Materials and methods. Since 2009 through 2016 72 patients with stage III and IV aged between 42 and 77 years underwent upfront surgery.Anatomical sites included 34 (46 %) tonsil, 24 (33 %) base of tongue and 14 (21 %) soft palate cases. Transcervical sparing the mandible,mandibulectomy and transoral approaches were used in 42 (58 %), 11 (15 %) and 7 (10 %) patient, respectively. Total glossectomy was performed in 4 (5.5 %) cases. Tumor extension necessitated extended laryngectomy in 8 patients (11.5 %). Primary closure of the pharyngeal wound was possible in 30 patients (42 %). Reconstruction with distant flaps was performed in the remaining 42 patients. Both free (anterolateral thigh – 19, radial forearm flap – 10) and flaps with axial blood supply (pectoralis major – 9, supraclavicular flap – 4) were used. There were 6 T1, 12 T2, 28 T3 and 20 T4 tumors; 62 patients were N-positive: N1 – 10 cases, N2 – 51, N3 – 1. Positive surgical margins were diagnosed in 13 cases (18 %) including 3 cases of R2 resection. Adjuvant radiation therapy with or without chemotherapy was completed in 45 patients (63.4 %). Survival was calculated according to Kaplan–Mayer method.Results. There was 1 death in early postoperative period. Mean follow-up for the remaining patients (n = 71) was 27 months (1–94). Median survival was 27 months (95 % CI 11.5–42.5); 3-year overall survival was 44 %; 33 out of 34 still alive patients are capable to take food orally. Only 1 (2.9 %) patient is gastrostomy tube dependent. Univariate analysis revealed that positive margins (p <0.0001) and completeness of combined treatment (p <0.01) are the main factors that have statistically significan impact on prognosis.Conclusion. Combined approach with upfront surgery is one of the main treatment modalities for advanced oropharyngeal cancer. Modern reconstructive options and strict adherence to a proper surgical technique give a high chance for a valuable rehabilitation for the vast majority of patients. Scrupulous planning of the resection of the primary tumor based on modern imaging techniques and encouraging patients to complete all prescribed treatments are the main physician-related factors that influence survival outcome.